Wykorzystanie technologii rozpoznawania twarzy w Chińskiej Republice Ludowej - Choińska, Zuzanna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
Technology is playing an increasingly important role in people’s lives which is associated with many benefits, including making life and functioning easier. On the other hand, its development also creates many risks for individuals, which makes the discussion on its legal regulation gain importance. The People’s Republic of China is characterized by a completely different approach to the development of technology and its regulation, as well as to the protection of personal data, than the approach known in the European Union. This article aims to present what impact the development and use of facial recognition technology in China has on compliance with fundamental law and the lives of its citizens. The analysis will be conducted by discussing the adopted legislation, today’s changes in the perception of the technology and the priorities adopted by the Chinese authorities.
Keywords: personal data; facial recognition technology; privacy; fundamental rights; human rights; biometric data; artificial intelligence